THE INFLUENCE OF SPX EXPRESS COURIER PERFORMANCE ON CONSUMER SATISFACTION IN RANAI KOTA: AN ISLAMIC PERSPECTIVE - Denny Yusrizal Denny; Kartubi; Said M. Rahimin (SOSIOEDUKASI, 2026)
This study aims to examine the influence of SPX Express courier service quality on consumer satisfaction in Ranai Kota, analyzed through an Islamic ethical perspective. Employing a quantitative associative approach, data were collected via a structured Likert-scale questionnaire distributed to purposively selected consumers who had directly used SPX Express services in the study area. Instrument validity and reliability were confirmed through Pearson Product Moment correlation and Cronbach's Alpha, while data analysis utilized simple linear regression supported by classical assumption tests. The findings confirm that service quality exerts a significant and positive influence on consumer satisfaction, with package security and courier responsibility identified as the strongest performance dimensions. However, timeliness and service communication remain areas of notable deficiency. From an Islamic perspective, the values of amanah and ihsan were found to substantively shape consumer satisfaction formation, functioning as a moral evaluative framework that moderates how technical service performance is perceived and assessed. These results indicate that in Muslim-majority consumer contexts, service excellence is both an operational and ethical imperative. The study contributes to SDG Goal 8 and SDG Goal 10 by demonstrating that ethically grounded service quality drives inclusive economic participation and dignified service delivery in regional markets.